A CROSS-SECTIONAL OBSERVATIONAL STUDY OF THE RELATIONSHIP BETWEEN NEUTROPHILS AND LYMPHOCYTES IN CORONARY ARTERY DISEASE (Journal of Pharmaceutical Negative Results, 2022)
Inflammatory indicators are traditional markers of inflammation in cardiovascular disorders, the leading cause of death worldwide (30%). The study will compare neutrophil and lymphocyte counts to coronary artery disease severity. October 2019 marked the beginning of patient registration 72 patients in total. Using the normal protocol, each individual was examined. Before the trial began, participants gave written consent. Interviews were done using a questionnaire containing questions regarding sociodemographic, addiction, the clinical profile, and other issues. The form also asked about past and present medical histories. When needed, sputum, blood, cerebrospinal fluid (CSF), pleural fluid, ascitic fluid, and pus cultures were used to diagnose infections. The entire database was developed in Excel. IBM SPSS Statistics 21.0 and Openepi 2.3.1 are used for all statistical studies. The percentage, mean, range, and standard deviation were used to describe the data. The Chi-square test and student t-test were employed to determine statistical significance for both qualitative and quantitative data. Therefore, a valuable measure for assessing the severity of coronary artery disease is the neutrophil-to-lymphocyte ratio.